Plant Biology 2010 Montreal, Kanada 31 Julai- 4 Ogos 2010 - T.P. Kannan, T.P. Kannan (Pusat Pengajian Sains Perubatan, 2010)
Genetic variation tor Alabidopsis th_aliana heterotic responses is in farge part explained by the epistl;ltic interaction of flowering time genes FRIGIDA and Flowering Locus C. Alltlbi.Qt!« ~istance .ot:.w!le<ltin .lh~ tprm .ot~.S.S!Z.R. k translocations Genomic <Jnalysis of cytosine methylation in Populus trichocarpa tissues from differing developmental stages Saturating Barley Malting Quality QTls with AG-Vs Transposons Chi_meric aneuploids and their role in the evolution of early generation allopolyploids of Arabidopsis Cornparative evolutionary analysis of the Hsp100/CipB proteins in photosynthetic and non-photosynthetic lineages. Anomalous segregation of DArT markers in barley doubled haploid popui<Jtions Nicotine biosynthesis originated by ancient lateral gene_ ··~- transfer from diverse eubacteriaJ phyla ~- The Age of Arabidopsis: dated molecular phylogenies indicate a Miocene origin for Arabidopsis Allelic variation among shoot maturation pathway genes regulates phenotypic diversity for vegetative phase change within maize populations An!llyses of Qatural variation in gene expression & association genetics studies of stress-related genes in loblolly pine (Pinus taeda !.,.) Molecular ~>Vents during apical bud formation in white spruce Investigating the. molecular mechanisms underlying the